2009
DOI: 10.1021/jf900239t
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Sensitive Analysis of Alkylresorcinols from Cereal Grains and Products Using HPLC−Coularray-Based Electrochemical Detection

Abstract: Alkylresorcinols (AR) present in the bran fraction of wheat, rye, and barley grains are of current interest as biomarkers of wholegrain cereal intake. This paper reports the development of a rapid quantitative HPLC method allowing sensitive analysis of AR in cereals in 14 min using coularray (CA) detection. The LOD was 1 ng injected and the LOQ 2.5 ng injected, whereas the intrarun and inter-run CVs were 0.8 and 6.4%, respectively. Analytical recovery determined by spiking ranged from 98 to 107% for AR homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 35 publications
3
61
0
2
Order By: Relevance
“…AR in food samples used during the intervention were extracted by using hot 1-propanol (1) and analyzed by using HLPC with Coularray electrochemical detection (2). The variation with replicate analyses was ,4%.…”
Section: Analytic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…AR in food samples used during the intervention were extracted by using hot 1-propanol (1) and analyzed by using HLPC with Coularray electrochemical detection (2). The variation with replicate analyses was ,4%.…”
Section: Analytic Methodsmentioning
confidence: 99%
“…4 are phenolic lipids found in high concentrations in the bran fraction of wheat and rye, in low concentrations in barley, and in only minute quantities in the endosperm (white flour) fraction of these cereals (1,2). ARs are mainly consumed via products containing WG wheat or rye or bran from these cereals.…”
Section: Arsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the HPLC method for the analysis of intact ARs in cereals using coularray detection (HPLC-CA) has been suggested. Use of the CA detector allowed detection of low concentrations of ARs in white wheat flour, which had not been reliably detected using previous methods (Ross and Kochhar, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…The alkyl chain in cereal ARs varies from 15 to 27 carbon atoms. They are located in the intermediate layers between pericarp and testa in the grain (Landberg et al, 2008), and are found in high concentrations only in whole grain and/or bran products of wheat (31.7-143.9 mg/100 g dry matter, DM) and rye (36.0-320.0 mg/100g DM), and in very small amounts in refined flour (white bread, most breakfast cereals, pasta) or in any other commonly consumed foods (Ross et al, 2003;Ross et al, 2004a;Ross and Kochhar, 2009;Annica et al, 2010). They are also present in triticale (43.9-64.7 mg/100 g DM), and in small amounts in barley (4.2-5.1 mg/100 g DM), but not in oats (Ross et al, 2003).…”
Section: Introductionmentioning
confidence: 99%